Effects of forest fragmentation on a guild of wintering passerines: the role of habitat selection - Tellería, J L; Santos, T (Biological conservation, 1995)
This study analyses the winter colonization of an archipelago of 31 forests (0.1-350 ha) in central Spain by the guild of pariforms (Parus, Aegithalos, Regulus, Sitta and Certhia). Two hypotheses are considered: (a) that birds with similar habitat preferences tend to disap- pear simultaneously with the reduction in forest size, leading to a ‘nested’ pattern of species distribution; or (6) that the species in the smallest forests are a random sample of those found in the larger ones. The results sup- port hypothesis (a). The species that depend on rela- tively scarce resources, such as tree trunks and junipers Juniperus thurifera (Sitta europaea, Certhia brachy- dactyla, Parus cristatus and P.ater) only occupied the largest forests. On the other hand, species that exploit abundant, ubiquitous resources, such as holm oak Quercus ilex foIiage (Regulus ignicapillus and Parus caeruleus), were distributed uniformly throughout all the fragments. These results emphasize the need for a better understand- ing of habitat selection by species when designing conser- vation strategies for fragmented populations.
Keywords: Forest fragmentation; habitat selection; Spain; wintering passerines